Avaliação do ecossistema microbiano de ratos wistar submetidos à carcinogênese química de cólon após o consumo de lactobacillus acidophilus crl 1014 e extrato aquoso - Avi, Camilla Martins [UNESP] (2014)
Colon cancer is one of the most prevalent types of cancer, and its etiology may be related to genetic, environmental factors and type of diet. Therefore, the food industry invests in the development of functional foods, such as probiotic bacteria and prebiotic ingredients. This research was evaluate the effects of consumption of probiotic (Lactobacillus acidophilus CRL 1014) and prebiotic (yacon extract) on the gut microbiota on 1.2 dimethylhydrazine (DMH) induced colon carcinogenesis in Wistar rats. The animals were randomly allocated into five groups (n=35): Treatment I-GCN: negative control animals (healthy animals + commercial feed); Treatment II-GCP: positive control animals (DMH induced + commercial feed); Treatment III-GPRO: (DMH induced + commercial feed + L. acidophilus CRL 1014); Treatment IV-GPRE: (DMH induced + commercial feed + yacon); Treatment V-GS: (DMH induced + commercial feed + L. acidophilus CRL 1014+ yacon). The induced animals were inoculated with DMH twice weekly for 2 weeks at a concentration of 40mg/kg weight. The probiotic, L. acidophilus CRL 1014 was administered in 109CFU/mL (3 ml/kg body weight) and the yacon extract (10% FOS/ feed),once daily. Microbiological analysis of Enterococcus spp., Lactobacillus spp., Bifidobacterium spp., Enterobacteriaceae, Clostridium spp., Bacteroides spp., total aerobes and facultative anaerobes were performed by plate count. Analysis of PCR-DGGE for the lactobacilli community, short-chain fatty acids (SCFA) production, ammonium ions and fecal pH were performed. The viable counts showed that the Enterococcus spp., at the end of the experimental protocol, the treated groups showed higher than controls count. The counts of Enterobacteriaceae and Bacteroides spp., were higher to GCP. There was an increase of Lactobacillus spp. for GPRO and Bifidobacterium ssp. for GPRE and GS. All groups increased counts facultative anaerobes, and GPRO was the only group that reduced total aerobes ...